ПРОЦЕДУРА ФОРМУВАННЯ ЕКОНОМІЧНИХ ПОНЯТЬ У СТАРШОКЛАСНИКІВ (Педагогіка вищої та середньої школи, 2022)
In the article, the structural components of scientific notions its basic conceptions of forming of economic notions at pupils of higher forms in the process of teaching are considered.